CD44/CD44v6 a reliable companion in cancer-initiating cell maintenance and tumor progression - Wang, Zhe; Zhao, Kun; Hackert, Thilo; Zöller, Margot (Frontiers in cell and developmental biology, 2018)
Metastasis is the leading cause of cancer death, tumor progression proceeding through emigration from the primary tumor, gaining access to the circulation, leaving the circulation, settling in distant organs and growing in the foreign environment. The capacity of a tumor to metastasize relies on a small subpopulation of cells in the primary tumor, so called cancer-initiating cells (CIC). CIC are characterized by sets of markers, mostly membrane anchored adhesion molecules, CD44v6 being the most frequently recovered marker. Knockdown and knockout models accompanied by loss of tumor progression despite unaltered primary tumor growth unraveled that these markers are indispensable for CIC. The unexpected contribution of marker molecules to CIC-related activities prompted research on underlying molecular mechanisms. This review outlines the contribution of CD44, particularly CD44v6 to CIC activities. A first focus is given to the impact of CD44/CD44v6 to inherent CIC features, including the crosstalk with the niche, apoptosis-resistance and epithelial mesenchymal transition. Following the steps of the metastatic cascade, we report on supporting activities of CD44/CD44v6 in migration and invasion. These CD44/CD44v6 activities rely on the association with membrane-integrated and cytosolic signaling molecules and proteases and transcriptional regulation. They are not restricted to, but most pronounced in CIC and are tightly regulated by feedback loops. Finally, we discuss on the engagement of CD44/CD44v6 in exosome biogenesis, loading and delivery. exosomes being the main actors in the long-distance crosstalk of CIC with the host. In brief, by supporting the communication with the niche and promoting apoptosis resistance CD44/CD44v6 plays an important role in CIC maintenance. The multifaceted interplay between CD44/CD44v6, signal transducing molecules and proteases facilitates the metastasizing tumor cell journey through the body. By its engagement in exosome biogenesis CD44/CD44v6 contributes to disseminated tumor cell settlement and growth in distant organs. Thus, CD44/CD44v6 likely is the most central CIC biomarker.